2018
DOI: 10.3389/fneur.2018.00960
|View full text |Cite
|
Sign up to set email alerts
|

Oculomotor Performances Are Associated With Motor and Non-motor Symptoms in Parkinson's Disease

Abstract: Background: Parkinson's disease (PD) patients exhibit deficits in oculomotor behavior, yet the results are inconsistent across studies. In addition, how these results are associated with clinical symptoms is unclear, especially in China.Methods: We designed a case-control study in China including 37 PD patients and 39 controls. Clinical manifestations in PD patients were recorded. Oculomotor performance was measured by a video-based eye tracker system.Results: We found that six oculomotor parameters, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 26 publications
(31 reference statements)
2
15
0
Order By: Relevance
“…Linder et al (2012) found a correlation between the axial UPDRS score and SPEM gain of their PD patients [12] . Zhang et al, 2016 found a correlation between SPEM gain and disease duration and UPDRS scores [19] .…”
Section: Disease Severitymentioning
confidence: 99%
“…Linder et al (2012) found a correlation between the axial UPDRS score and SPEM gain of their PD patients [12] . Zhang et al, 2016 found a correlation between SPEM gain and disease duration and UPDRS scores [19] .…”
Section: Disease Severitymentioning
confidence: 99%
“…Anomalies are more evident for voluntary saccades, in early stages of disease (for review, see Pretegiani & Optican, 2017 ). A behavioral study ( Zhang et al, 2018 ) showed that PD is linked to reduced fixation stability when fixation is required. Conversely, during free viewing of single images, PD patients make fewer saccadic eye movements, and within a more narrow range.…”
Section: Discussionmentioning
confidence: 99%
“…From a theoretical perspective, identifying neural systems controlling eye movement during rest could allow better partitioning between relatively more ‘active,’ (oculo)motor-related aspect of RS as opposed to other more covert, nonmotor-related aspects of RS. Finally, eye movements themselves could be a possible confounder when studying healthy and clinical populations that differ in oculomotor control, including autism (e.g., Takarae, Minshew, Luna, Krisky, & Sweeney, 2004 ), Parkinson’s disease (e.g., Pretegiani & Optican, 2017 ; Zhang et al, 2018 ), or schizophrenia (e.g., Dowiasch et al, 2016 ; Morita, Miura, Kasai, & Hashimoto, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of ocular motor difficulties have shown that prolongation of saccade latency is one of the most quantitative ocular motor measurements in idiopathic PD and in atypical parkinsonian syndrome. 15 , 16 , 17 Saccades are fast eye movements used to explore the visual world. 18 Saccades can be divided into reflexive saccade, in response to a target, or volitional saccade, which is self-generated.…”
Section: Introductionmentioning
confidence: 99%
“…Prolonged reflexive saccade latencies correlate with older age, longer disease duration, and greater severity of disease. 15 , 16 , 17 Although the effect of dopamine replacement on reflexive saccade latencies has been mixed, 19 , 20 , 21 treatment has been shown to improve the latency of volitional saccades. 19 , 20 , 21 , 22 , 23 Subthalamic deep brain stimulation has also been shown to improve saccade latencies.…”
Section: Introductionmentioning
confidence: 99%